Self management pilot study on women with breast cancer: lessons learnt in Malaysia - Loh, S.Y.; Yip, C.H.; Packer, T.; Quek, K.F. (West Asia Organization for Cancer Prevention, 2010)
Objective: With increasing survival rates, breast cancer is now considered a chronic condition necessitating innovative care to meet the long-term needs of survivors. This paper presents the findings of a pilot study on self-management for women diagnosed with breast cancer and their implications for Asian health care providers. Methods: A pre-test/ post-test pilot study was conducted to gain preliminary insights into program feasibility and barriers to participation, and to provide justification for a larger trial. Results: The study found the 4 week self-management program feasible and acceptable, with a favourable trend in quality of life. The recruitment barriers ranged from competing medical appointments, uncollaborative health providers, linguistic barriers and social-household concerns. Supporting facilitators identified were family, health professionals and fellow participants ("buddies"). Lessons from the study are discussed with regard to Asian health providers. Conclusion: There is preliminary evidence that self management is a workable and potentially useful model even in an Asians entrenched-hierarchical medical model of care. The initial challenge was breaking down barriers in acceptancee of a collaborative stance. A clinical trial is now warranted to gather more evidence.